TACI and BTK gene analysis in predominantly antibody deficiencies among the primary immunodeficiency disorder patients in Bangladesh - Chakrobortty, Tripty; Roy, Chandan Kumar; Islam, Mohammad Imnul; Niger, Ismet; Laila, Kamrul; Sarker, Avizit; Juyee, Nusrat Akhtar; Islam, Md. Mydul; Hoque, Fahmida; Chakrobortty, Partho Protim; Ahmed, S. M. Ali; Sattar, Abu Naser Ibne (Frontiers in Medicine, 2025)
BackgroundCommon variable immune deficiency disorder (CVID) and X-linked agammaglobulinemia (XLA) are the most prevalent predominantly antibody deficiencies (PADs). Analysis of the TACI/TNFRSF13B gene in CVID and BTK genes in XLA patients using Sanger sequencing can help make specific diagnoses of these cases. The study aimed to find the TACI and BTK gene mutations and their allelic variations associated with CVID and XLA patients.MethodsThis cross-sectional study was conducted on clinically suspected PAD patients who attended the Department of Pediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh, from September 2022 to August 2023. Serum immunoglobulin levels, immunophenotyping by flow cytometry, and PCR were conducted in the Department of Microbiology and Immunology at BSMMU. Genetic analysis of the TACI and BTK genes was conducted using Sanger sequencing at DNA Solutions Limited, Dhaka, Bangladesh. The sequencing results were validated using the NCBI GenBank.ResultsOf 35 clinically suspected PAD patients, 15 (42.86%) were diagnosed as PAD patients. Within this group, seven (46.67%) were diagnosed with CVID, seven (46.67%) with XLA, and one (6.66%) with agammaglobulinemia other than XLA. The analysis of the TACI gene revealed no pathogenic variants in the CVID patients. Upon analyzing exons 2 to 19 of the BTK gene, seven pathogenic/likely pathogenic mutations were detected, consisting of four nonsense and three missense mutations. Among these, three were found to be novel mutations, including two missense and one nonsense mutation.ConclusionThe genetic analysis of the TACI gene in CVID patients revealed no pathogenic variants. The BTK gene displayed heterogeneous mutations, with nonsense mutations being the most prevalent. In this cohort, XLA patients presented three de novo point mutations.